Growth performance of two lemon [Citrus limon (L.) Osbeck] cultivars budded on three rootstocks, Gezira State, Sudan - B. H. Abdallah, Halaa; E. Elkashif, Mohammed; A. Eljack, Ali; B. Dafaallah, Awadallah (Gezira Journal of Agricultural Science, 2021)
Lemon [ Citrus limon (L.) Osbeck ], family Rutaceae, is one of the world's major fruit crops with global popularity contributing to human diets. Lemon rootstocks and scion cultivars play an important role in the rapid development of citrus in the world. This study was conducted to evaluate the growth performance of two lemon cultivars budded on three rootstocks under Gezira State conditions, Sudan. The experiment was conducted in the nursery of the Department of Horticultural Sciences, Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, in 2017.Volcamariana, Rough Lemon and Macrophylla rootstocks were grafted with buds of Eureka and Teresa cultivars. The T- budding technique was used in this study. Treatments were arranged in a randomized complete block design with three replicates. Parameters measured were rootstock height and thickness, height of scion, number of branches, length of branches and stem circumference of the scion. The parameters were recorded for 10 months.  Rootstocks were significantly different in their vegetative growth.  Rough Lemon rootstock resulted in the best vegetative growth.  However, there were no significant differences in growth parameters between Volkameriana and Macrophylla rootstocks. Lemon cultivars were highly significantly different in their vegetative performance. Teresa lemon cultivar resulted in the largest plant height (73.9 cm), number of branches (27), length of branches (68 cm) and stem circumference (11.8 cm). The interaction effects of rootstocks and cultivars on vegetative performance of lemon were significant. The largest plant height (84.33 cm), number of branches (31.7), length of branches (75.7 cm) and stem circumference (12.3 cm) were obtained by Teresa cultivar budded on Rough Lemon rootstock and the smallest parameters were obtained by Eureka cultivar budded on Volkameriana, whereas the smallest length of branches (55.3) and stem circumference (9.5 cm) were obtained by Eureka cultivar budded on Macrophylla. Depending on the results of this study, it is recommended to bud the lemon cultivar Teresa on Rough Lemon rootstock under Gezira State Conditions, to obtain the best growth performance.